Perception of healthcare workers and end-users about the implementation of the Abiye Scheme in Ondo State, Nigeria (2022)
Background: To upturn the poor maternal, children and neonatal health indicators in a South-west Nigerian state, the Abiye Scheme was inaugurated in 2009. This study assessed the perception of healthcare workers and end-users in Ondo State about the implementation of the four strategies proposed to actualise this scheme. Methods: This qualitative study employed the use of 15 key informant interviews (KIIs) conducted among 15 healthcare workers and eight focus group discussions (FGDs) conducted among 72 pregnant and nursing mothers to generate essential data. The Abiye scheme strategies assessed were the establishment of a health insurance scheme; utilization of health rangers (HR); upgrade and renovation of peripheral health facilities; and establishment of mother and child hospitals. All interviews were audio-recorded, transcribed verbatim, coded, and analysed with Nvivo 10 software using framework analysis via deductive methods. Results: The study respondents perceived the Abiye scheme as a well-conceptualized program with good intentions. Only the establishment of the mother and child hospitals strategy of the Abiye scheme was perceived to be properly implemented by our study respondents. According to the respondents, the health insurance scheme was nearly non-existent. Conclusion: Abiye scheme is undisputedly a well conceptualized program that has impacted positively its users. Nonetheless, the laid down strategies have not been fully implemented. To achieve maximal impact, the health rangers must be enabled to perform their duties; the health insurance component must be strengthened and properly implemented; and the peripheral health facilities should be quickly and actively co-opted into the scheme.